Assignment: Outline - Hoadley, Sarah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Now that you have your research question and your four empirical resources, the next stage is constructing an outline of what you will cover in your research paper. This will be a detailed outline typed no longer than two pages. Make sure to include your name and id number at the top right hand corner of your outline assignment. The outline assignment will be worth a possible 3 points toward your research paper and presentation total.